2022
DOI: 10.1155/2022/5873846
|View full text |Cite|
|
Sign up to set email alerts
|

Image Simulation of Traditional Village Spatial Layout Based on Computer Numerical Analysis

Abstract: In order to solve the problems of insufficient protection and spatial development of traditional villages, a method of spatial layout of traditional villages based on computer numerical analysis is proposed. This method uses GIS technology to determine the spatial distribution characteristics of traditional villages in a city by using the nearest neighbor index, geographic concentration index, and kernel density estimation, and analyzes its influencing factors. The experimental results show that most tradition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
(16 reference statements)
0
6
0
Order By: Relevance
“…The geographical concentration index is G = 32 > 18.73 [28], which shows that the traditional villages in Hebei Province are concentrated at the prefecture-level city level and the degree of concentration is high. Using the kernel density analysis tool of ArcGIS [28], we can also conclude that the spatial distribution of traditional villages in Hebei Province is highly aggregated (seeFigure 4) [41]. The core areas of Shijiazhuang and Xingtai-Handan are very weakly connected, while the other prefecture-…”
Section: Analysis Of Spatial Distribution Concentration and Homogeneitymentioning
confidence: 91%
See 2 more Smart Citations
“…The geographical concentration index is G = 32 > 18.73 [28], which shows that the traditional villages in Hebei Province are concentrated at the prefecture-level city level and the degree of concentration is high. Using the kernel density analysis tool of ArcGIS [28], we can also conclude that the spatial distribution of traditional villages in Hebei Province is highly aggregated (seeFigure 4) [41]. The core areas of Shijiazhuang and Xingtai-Handan are very weakly connected, while the other prefecture-…”
Section: Analysis Of Spatial Distribution Concentration and Homogeneitymentioning
confidence: 91%
“…where R denotes the index of the nearest point, n refers to the number of points, A represents the area of the region and D reflects the density of the point [31]. A value of R equalling 1 indicates that the point elements are distributed randomly [41]; a value of R less than 1 denotes a condensed distribution of point elements, whereas a value greater than 1 indicates a uniform distribution. The intention was to utilize the closest neighbourhood index as a tool to assess the historical clustering and spatial relationships of traditional villages within their respective dynastic periods.…”
Section: The Nearest Neighbour Index Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…As a comprehensive art, landscape design integrates knowledge from multiple fields, such as architecture, landscape, and plants, aiming to create an artificial environment with aesthetic value, ecological function, and practicality. In traditional Chinese garden design, landscape painting plays a crucial role, and its unique artistic techniques and aesthetic concepts provide rich sources of inspiration for garden design (Li & Zhang, 2022). Traditional Chinese landscape painting holds a profound definition and significance within the context of this study.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have revealed that most traditional villages in China, except for those in Yunnan and Tibet areas, are mainly distributed in areas with lower altitude and flat slope [17], with a topographic relief ranging from 100 m to 300 m. However, there are still a few traditional villages distributed in high-altitude areas, such as Tongren Tibetan traditional villages in Qinghai Province. Currently, for traditional villages in Shaanxi Province, previous studies mainly focus on the landscape system [20], village architecture [21], spatial distribution [22], specific village structure, and village landscape gene. However, there is a lack of macroscopic and comprehensive analysis, especially for different geographical locations and regional cultures.…”
Section: Introductionmentioning
confidence: 99%